Development of a non-domestic building refurbishment scheme for Malaysia: A Delphi approach. (15th January 2019) - Kamaruzzaman, Syahrul Nizam; Lou, Eric Choen Weng; Wong, Phui Fung; Edwards, Rodger; Hamzah, Noraini; Ghani, Mohd Khairolden
Abstract: Building refurbishment is a key in promoting environmentally sustainable development due to its potential for reducing greenhouse gas emissions and energy consumption associated with existing buildings. The general metrics for assessing the impacts of refurbishment have not been established for existing buildings in most of the countries. In Malaysia, there is currently no single environmental assessment scheme for building refurbishment. The existing environmental assessment schemes are not sufficiently robust, as they do not include factors such as quality of services and economics. It is essential to have a customised suite of sustainability schemes specifically designed for the Malaysian context to facilitate best practice for non-domestic refurbishment assessment. A comprehensive Delphi process was developed to assist in the identification of suitable assessment schemes for use in non-domestic buildings. Three successive rounds of surveys were conducted with ten Delphi experts with expertise in sustainability and green assessment. The study revealed that energy related factors such as air-conditioning were ranked as the most important assessment theme for refurbishment, followed by indoor environmental quality and water assessment. The findings of this research will be used to develop a weighting system by using the analytic hierarchy process in the next research stage, leading to a complete refurbishment environmental assessment scheme. Highlights: Refurbishing of non-domestic buildings could achieve sustainability. There is lacking of an individual refurbishment scheme in various regions. Energy ranked the highest, followed by indoor environmental quality and water. Quality of services and economic are important for refurbishment practice.